Crystal growth, dielectric studies, charge transfer and ionic hydrogen-bonding interactions of L-arginine hydrobromide monohydrate single crystal: A novel third order nonlinear optical material for optoelectronic applications. (May 2020) - John, Jerin Susan; Saravana Kumar, M.; Joy, Lija K.; Sajan, D.; Vinitha, G.; Vijayan, N.; John, Nimmy L.
Graphical abstract: Highlights: Large crystals of semi-organic material LAHBr are synthesized and grown by slow evaporation method. Hydrogen-bonded system of LAHBr is studied theoretically using Gaussian'09 program suite. The charge transfer in the system leads to the nonlinear optical behaviour of the material. Abstract: DFT computations supported by B3LYP/cc-pVTZ level theory have been employed to derive equilibrium geometry, vibrational wavenumbers and the hyperpolarizability values of the nonlinear optical (NLO) material L-Arginine Hydrobromide monohydrate (LAHBr). Changes in the atomic charge distribution among different groups due to the presence of strong electronegative atoms and the attenuation of O-H bonds of water molecule have been analyzed. H-bonding effects of LAHBr are examined with the aid of structural analysis, IR, Raman vibrations and NBO analysis. The occurrence of strong intra- and intermolecular NH⋯O, NH⋯Br and OH⋯O ionic hydrogen bonding and non-bonded interactions in making the LAHBr unit NLO active has been discussed. The charge transport mechanism is analyzed by using dielectric measurements and the obtained results suggest good quality of the crystal.